THE PHENOMENON OF SOCIAL MYTHOLOGY IN THE MODERN SCIENTIFIC DISCOURSE OF UKRAINE - Вусатюк, А. О. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
The article is devoted to the analysis of modern scientific works in Ukraine, which investigates the phenomenon of social mythology. Identified the main directions of studying of social mythology and the most topical issues. Analyzed characteristics, strong points and weaknesses in the study of social mythology in modern Ukrainian scientific discourse. Outlined prospects of subsequent research of social mythology.